FRI0491 Incidence and Predictors of Cutaneous Manifestations During the Early Course of Systemic Sclerosis – A 10 Year Longitudinal Study from the Eustar Database. (9th June 2015) - Jaeger, V.K.; Wirz, E.G.; Allanore, Y.; Riemekasten, G.; Hachulla, E.; Distler, O.; Airò, P.; Carreira, P.E.; Tikly, M.; Vettori, S.; Balbir Gurman, A.; Damjanov, N.; et al.
Abstract : Background: Systemic sclerosis (SSc) is a multisystem autoimmune disorder with skin sclerosis and digital ulcers (DU) as typical cutaneous lesions. Patients are categorised as having either limited or diffuse skin involvement, depending on the distribution of skin sclerosis which is important as diffuse cutaneous SSc is associated with higher morbidity and mortality. Objectives: Given the paucity of pivotal data on the temporal evolution of skin manifestations during the early course of SSc, our aim was to longitudinally map the onset and identify risk factors for skin sclerosis and DU in patients with SSc from an early time point after the onset of Raynaud's phenomenon (RP) in the EUSTAR cohort. Methods: SSc patients followed in the prospective multinational EUSTAR database were investigated if they had a baseline visit within one year after RP onset. Outcome measures were analysed as a function of time after RP onset using Kaplan-Meier methods and included the evolution of the modified Rodnan skin score (mRSS), the presence of skin sclerosis, the presence of diffuse cutaneous involvement and the presence of DU. Cox proportional hazards regression analysis was used to evaluate risk factors. Results: 707 SSc patients in the EUSTAR database had a baseline visit within one year after RP onset. The median peak mRSS was 15 points and was reached 1.0 years after RP onset. There was no difference in the median time to reach the mRSS peak between patients with limited and patients with diffuse cutaneous SSc (p=0.36). All patients who developed moderate to severe skin sclerosis (defined as a mRSS≥2 at any body area) did so within 6.5 years after RP onset. The 1-year probability to develop a mRSS≥2 in at least one area of the upper and lower extremities was 68% and 25%, respectively. A quarter of patients developed diffuse cutaneous involvement in the first year after RP onset (Figure 1 ). This probability increased to 35.4% during the subsequent two years. Only a minority of patients developed diffuse cutaneous SSc thereafter. The probability to develop DU increased continuously to a maximum of 70% at the end of the 10 year observation. The main risk factors for diffuse cutaneous SSc were the presence of anti-RNA polymerase III autoantibodies, followed by anti-topoisomerase autoantibodies and male sex. The main risk factor for incident DU was the presence of anti-topoisomerase autoantibodies. Conclusions: Early after RP onset, cutaneous manifestations exhibit rapid kinetics in SSc. This should be accounted for in trials aiming to prevent skin worsening. Furthermore, our findings will enable physicians to counsel and manage patients presenting early more accurately. Acknowledgements: EUSTAR acknowledges the prior support that EULAR has provided for the maintenance of the EUSTAR database. Disclosure of Interest: V. Jaeger: None declared, E. Wirz: None declared, Y. Allanore Grant/research support from: Actelion, Bayer, Biogen Idec, BMS, Genentech/ Roche, Inventive, Medac, Pfizer, Sanofi/Genzyme, Servier and UCB, Consultant for: Actelion, Bayer, Biogen Idec, BMS, Genentech/ Roche, Inventive, Medac, Pfizer, Sanofi/Genzyme, Servier and UCB, G. Riemekasten: None declared, E. Hachulla: None declared, O. Distler Grant/research support from: 4D Science, Actelion, Active Biotec, Bayer-Schering, Biogen, Biovitrium, BMS, Boehringer Ingelheim Pharma, EpiPharm, Ergonex, GSK, Inventiva, Medac, Novartis, Pfizer, Pharmacyclics, Roche/Genentech, Sanofi/Genzyme, Serodapharm, Sinoxa and United BioSource Corporation., Consultant for: 4D Science, Actelion, Active Biotec, Bayer-Schering, Biogen, Biovitrium, BMS, Boehringer Ingelheim Pharma, EpiPharm, Ergonex, GSK, Inventiva, Medac, Novartis, Pfizer, Pharmacyclics, Roche/Genentech, Sanofi/Genzyme, Serodapharm, Sinoxa and United BioSource Corporation., P. Airò: None declared, P. Carreira: None declared, M. Tikly: None declared, S. Vettori: None declared, A. Balbir Gurman: None declared, N. Damjanov: None declared, U. Müller-Ladner: None declared, J. Distler: None declared, M. Li: None declared, P. Häusermann: None declared, U. Walker: None declared